Concept Development Method: Didactic intervention for the correct integration of science concepts in the conceptual network of students of the Primary Education Degree - Villalba Delgado, Yaiza Adaya; Quijano López, Rocío; Pérez Navío, Eufrasio (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The main objective of this work is to analyze the improvement of the learning difficulties of the students who are currently doing the Degree of teachers of Primary Education, through a didactic proposal of intervention, on the acquisition and conformation of concepts related to the Sciences. specifically covering the subject of the individual-environment relationship, through the application of the Concept Development didactic method. The study reveals that after the implementation of this method, science concepts are reinforced, as well as their teaching is improved, for future students in the classroom.